Analisis Kinerja Keuangan PT. Tembaga Mulia Semanan, TBK Tahun 2022 dan 2023 - Swadana, Ardha Pramudita; Devitamalia Angela Anjas Putri; Erwan Hermawan (Pusat Riset dan Inovasi Nasional, 2025)
Abstract. This study aims to determine the comparison of financial analysis based on the financial aspects of PT Tembaga Mulia Semanan, Tbk for the years 2022 and 2023. This type of research is descriptive quantitative. The variable used is an independent variable or a single variable. The data collection technique used is documentation technique from PT Tembaga Mulia Semanan, Tbk in the form of financial reports for the periods of 2022 and 2023. The data analysis technique used in this study is by calculating each indicator in the financial aspects.